2016
DOI: 10.1177/0013161x15616863
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leadership on Student Outcomes

Abstract: Purpose: This article illustrates how successful leaders combine the too often dichotomized practices of transformational and instructional leadership in different ways across different phases of their schools’ development in order to progressively shape and “layer” the improvement culture in improving students’ outcomes. Research Methods: Empirical data were drawn from a 3-year mixed-methods national study (“Impact Study”) that investigated associations between the work of principals in effective and improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
243
0
45

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 556 publications
(297 citation statements)
references
References 36 publications
9
243
0
45
Order By: Relevance
“…They concluded that "when transformational and shared instructional leadership coexist in an integrated form of leadership, the influence on school performance, measured by the quality of its pedagogy and the achievement of its students, is substantial" (p. 370). This view is supported by other researchers who have used terms such as "leadership for learning" (Heck & Hallinger, 2014) [3] and leadership "layering" (Day et al, 2016) [1]. Despite using different terminology, this research concurs that effective leadership should include both the teaching and learning foci of instructional leadership, and the capacity-building [5].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…They concluded that "when transformational and shared instructional leadership coexist in an integrated form of leadership, the influence on school performance, measured by the quality of its pedagogy and the achievement of its students, is substantial" (p. 370). This view is supported by other researchers who have used terms such as "leadership for learning" (Heck & Hallinger, 2014) [3] and leadership "layering" (Day et al, 2016) [1]. Despite using different terminology, this research concurs that effective leadership should include both the teaching and learning foci of instructional leadership, and the capacity-building [5].…”
Section: Discussionsupporting
confidence: 74%
“…These foci include the value of creating clear educational goals, planning the curriculum, and evaluating the quality of teachers and their teaching. This model infers that a principals' efforts should be concentrated on the promotion of better outcomes for students, and the importance of improving the quality of classroom teaching and learning (Day et al, 2016) [1]. More specifically, Hallinger (2003) [10] conceptualized instructional leadership as involving three key goals: 1) defining the school's goals, 2) supervising the delivery of the curriculum, and 3) encouraging a positive school learning environment.…”
Section: Instructional and Transformational Leadership Theoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…En concreto, existe una línea de investigación sobre cómo son los líderes de las escuelas exitosas (Day, 2016b(Day, , 2017Day, Gu, & Sammons, 2016; Moos, Johansson, & Day, 2011 …”
unclassified